2019
DOI: 10.1200/jco.2019.37.15_suppl.e17109
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of distant metastases in patients with endometrial carcinoma: A SEER population-based analysis.

Abstract: e17109 Background: Endometrial carcinoma is the most common gynecology malignancies in the worldwide. The clinical outcome of endometrial carcinoma is excellent, with disease specific survival rate over 90% in early stages. However, the prognosis of metastatic endometrial carcinoma is poor and the pattern of distant metastases has not been well characterized. In the present study, we sought to assess the incidence and prognosis of different distant metastatic sites in endometrial carcinoma. Methods: Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Once in the bloodstream, the tumour cells circulate throughout the body. They can then extravasate or exit the bloodstream at distant sites 6. After extravasation, tumour cells can colonise new tissue, in this case, the skin and nail bed of the finger 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once in the bloodstream, the tumour cells circulate throughout the body. They can then extravasate or exit the bloodstream at distant sites 6. After extravasation, tumour cells can colonise new tissue, in this case, the skin and nail bed of the finger 7.…”
Section: Discussionmentioning
confidence: 99%
“…After extravasation, tumour cells can colonise new tissue, in this case, the skin and nail bed of the finger 7. Certain tumours exhibit a tropism for specific tissues; molecular interactions between tumour cells and the microenvironment of the metastatic site might play a role in this selective colonisation 6 8. Additionally, factors such as tumour-induced immunosuppression could contribute to this phenomenon 7…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial cancer is the most common gynecologic cancer in developed countries 1 , and its incidence is also rapidly increasing 2 . Endometrial cancer is mostly diagnosed at an early stage 3 ; however, for women with advanced-stage cancers, the prognosis is poor 4 , and lymph node (LN) metastasis status is greatly related to the outcome of the disease 5 . Additionally, LN metastasis status can help identify patients who require adjuvant therapy and select the most efficacious treatment 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In a single-institution retrospective review of recurrent EC, the most frequently observed sites of relapse were lymph nodes (46 %), vagina (42 %), peritoneum (28 %) and lung (24 %) ( Sohaib et al, 2007 ). Surveillance, Epidemiology and End Result (SEER) population-based studies of patients with EC reported the most common sites of distant metastases were lung (1.5–1.8 %), followed by liver (0.8–0.9 %), bone (0.6–0.7 %), and brain (0.2 %) ( Li et al, 2019 , Mao et al, 2020 ). The molecular processes underpinning distant metastasis in EC are not well understood.…”
Section: Introductionmentioning
confidence: 99%